Three‐Dimensional Printed Prosthesis Reconstructs Bilateral Type III Pelvic Defect After Malignant Tumors Resection - Xuanhong He; Yi Luo; Chang Zou; Minxun Lu; Yuqi Zhang; Zhuangzhuang Li; Guy Romeo Kenmegne; Yong Zhou; Li Min; Chongqi Tu (Orthopaedic Surgery)
ABSTRACT Objective Type III hemipelvectomy and reconstruction are challenging. Several reconstruction options, including autologous soft tissue, prosthesis patch, autologous, or allograft, were reported, but a variety of shortcomings limited their application. Three‐dimensional (3D)‐printed prosthesis was designed to reconstruct the unilateral Type III pelvic defect and had favorable clinical outcomes. However, the reconstruction method for bilateral Type III pelvic defect was few reported. This study aims to design a bilateral pubis prosthesis and evaluate the early clinical outcomes and complications. Methods We retrospectively collected patients receiving 3D‐printed bilateral pubis prosthesis reconstruction after malignant tumor resection between 2017 and 2021. Demographics, anatomic data, operation time, blood loss, and clinical outcomes of patients were analyzed. The Musculoskeletal Tumor Society‐93 (MSTS‐93) score was performed to evaluate the function and complications were recorded. Results Four patients, including three for females and one for males, were enrolled in this study. Prosthesis was designed according to the pelvic anatomical data. The mean operation time and blood loss were 308.8 min (range, 240–400 min) and 655 mL (range, 400–1100 mL), respectively. The average follow‐up was 15.5 months (range, 12–16 months). The mean MSTS was 28.5 (28–29). One patient had incision necrosis postoperatively. No hernia, prosthesis displacement, or implant failure occurred during follow‐up. Four patients with 15 interfaces showed good osteointegration. Conclusions 3D‐printed bilateral pubis prosthesis could restore the integrity and stability of pelvic ring and improve limb function. Meanwhile, this reconstruction option provided a rigid bony‐soft support to prevent the development of hernia. In all, 3D‐printed bilateral pubis prosthesis is recommended to be a favorable selection for Type III pelvic defect reconstruction.